Application of Chemometrics Tools to the Study of the Fe(III)–Tannic Acid Interaction - Berto, Silvia; Alladio, Eugenio (Frontiers in Chemistry, 2020)
Chemometric techniques were applied to the study of the interaction of iron(III) and tannic acid (TA). Modelling the interaction of Fe(III) - TA is a challenge, as can be the modelling of the metal complexation upon natural macromolecules without a well-defined molecular structure. The chemical formula for commercial TA is often given as C76H52O46, but in fact it is a mixture of polygalloyl glucoses or polygalloyl quinic acid esters with the number of galloyl moieties per molecule ranging from 2 up to 12. Therefore, the data treatment can not be based on just the stoichiometric approach. In this work, the redox behavior and the coordination capability of the TA towards Fe(III) were studied by UV-vis spectrophotometry and fluorescence spectroscopy. Multivariate Curve Resolution-Alternating Least Squares (MCR-ALS) and Parallel Factor Analysis (PARAFAC) were used for the data treatment, respectively. The pH range in which there is the redox stability of the system Fe(III)-TA was evaluated. The binding capability of TA towards Fe(III), the spectral features of coordination compounds and the concentration profiles of the species in solution as a function of pH were defined. Moreover, the stability of the interaction between TA and Fe(III) was interpreted through the chemical models usually employed to depict the interaction of metal cations with humic substances and quantified using the concentration profiles estimated by MCR-ALS.